CORRECTION-DEVELOPMENTAL DIRECTION OF CURATIVE PHYSICAL-TRAINING LESSONS AT SPECIAL SCHOOL FOR CHILDREN WITH GRAVE SIGHT DISTURBANCES - Одинченко, Игорь; Одинченко, Лариса (SWorldJournal, 2020)
The results of theoretical investigation of the problem of space orientation development in junior schoolchildren suffering from grave sight disturbances are enlightened in the article. It is defined that correctional bent of pedagogical work in space ori